Implanter technique in hair transplant surgery always a surgical challenge for the operating surgeon - A prospective randomized study assessment - Moharana, Prateeksha; Bhaskaran, Rajprakash (Aesthetic Medicine, 2024)
Background: hair transplant surgery has evolved significantly, with the implanter technique gaining attention due to its purported advantages over traditional methods. However, the ability of the surgeon to adapt to this technique is always a challenge, and also achieving density in the recipient area becomes difficult and patient satisfaction all plays at most importance in a successful success of hair transplant surgery using implanters. Objectives: to evaluate the challenges of the implanter technique of Hair Transplant surgery in terms of number of grafts placed per cm square and patients satisfaction with a grade range from 1 to 3 wherein 1 being the poor satisfaction and 3 being good satisfaction. Materials and methods: this study aimed to evaluate the efficacy and challenges of the implanter technique compared to conventional needle methods. Patients were randomly assigned to either technique, and outcomes such as graft survival rates, procedure duration, and patient comfort were measured. Results: the results of this study show that the number of grafts present within a 1 cm2 box were 27-35 irrespective of the number of follicles. Patient satisfaction terms were assessed on a score grade from 1 to 3, with 1 being poor satisfaction, 2 being moderate satisfaction and 3 being good satisfaction. An assessment was done immediately post op and after 1 month of surgery. Conclusion: this study concludes that according to ISHR (International Society of Hair Restoration) a density of 80-100 grafts per 1 cm square is required. In this study it is reduced to around 27-35 grafts per 1cm2 box in the implanter technique. Furthermore, the patient’s satisfaction is at grade level of 2 showing that it is moderate. To increase the efficacy and outcomes of the implanter technique, further studies have to be conducted to increase the number of grafts per centimeters square and patients.